Genetic and Environmental Influences on Decoding Skills – Implications for Music and Reading - Centanni, Tracy M.; Anchan, D. M.; Beard, Maggie; Brooks, Renee; Thompson, Lee A.; Petrill, Stephen A. (Frontiers in Psychology, 2019)
Music education is associated with increased speech perception abilities and anecdotal evidence suggests musical training is also beneficial for performance in a variety of academic areas. In spite of this positive association, very little empirical evidence exists to support this claim except for a few studies linking musical training to improvements in verbal tasks. We evaluated the relationships between specific aspects of musical training/ability and scores on a series of standardized reading assessments in a sample of twins. There was a significant and positive relationship between self-reported sight-reading ability for sheet music and performance on passage comprehension- a standardized reading measure that relies on decoding and working memory. This effect was specific to sight reading ability, as other musical variables, such as number of years of practice or music theory, were not related to performance on this reading measure. Surprisingly, the verbal working memory ability we tested did not mediate this relationship. To determine whether there is a genetic component to these skills, we compared these relationships in pairs of monozygotic twins compared to dizygotic twins. Interestingly, intraclass correlations (ICC) for sight reading and passage comprehension were both higher in monozygotic twins compared to dizygotic twins, though this effect was larger for passage comprehension than for sight reading. These results together suggest a familial and potentially partially shared inherited mechanism for success in both musical sight-reading ability and passage comprehension.